PENGARUH PERBEDAANKADAR LOGAM BERATKROMIUM (Cr) TERHADAPPERTUMBUHAN POPULASISpirulina platensis (Gomont) Geitler DALAM SKALA LABORATORIUM - Ahmad Yusuf Afandi; Tri Retnaningsih Soeprobowati; Riche Hariyati (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2014)
Industrial products such as metal and paint had generate hazardous wastes, one of then is a heavy metal Chromium (Cr). Industrial wastes containing Cr may cause many negative effects when directly discharged to environment without any prior processing. Therefore, recovery actions (remediation) is one of many ways to solve the problem. Phycoremediation is one of remediation that is simple, efficient and safe in process by using the microalgae to remediate the environment, and one of the microalgae is Spirulina platensis (Gomont) Geitler. This study was conducted to determine the effect and the removal efficiency of heavy metals Cr on Spirulina platensis culture media. The results showed there was significant influence between the administration of heavy metal Cr 1 mg/l, 3 mg/l and 5 mg/l Cr on the population growth of S. platensis. Heavy metal Cr concentration of 1 mg/l increased the growth of S. platensis, while the opposite happened when administrated with 3 mg/l and 5 mg/l. Higher concentration of heavy metal Cr on culture media decreased population of S. platensis. The culture added with heavy metal Cr concentration of 1 mg/l, 3 mg/l and 5 mg/l on the 7 days treatment were able to decrease heavy metal Cr level respectively 35%, 14% and 8%. Thus, the longer treatment days the bigger decrease percentage concentration of heavy metal Cr. Keywords: Cr, phycoremediation, microlagae, Spirulina platensis